UTILIZATION OF TECHNOLOGY IN THE ADVANCEMENT OF LEARNING REFORM IN ELEMENTARY SCHOOLS - Huda, Hisbullah (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
The development of information technology facilitates communication and exchange of information so that place, time and distance are no longer constraints. The rapid development of information technology cannot be separated from the development of computer engineering. Advances in the field of computers and information technology also have a positive impact on the world of education. The application of most influential in the field of computer technology and information technology in education is the use of computer networks and the internet. With the internet, information services for target students are not limited by space, place, time and distance. Internet information services can be provided as a learning resource, learning media that can be studied according to the speed of student learning. The positive influence of using the internet for education in building human resources in education must be able to keep up with developments in the application of science and technology. Applications cover the industrial world so that graduates can meet the competency demands of the world of work. Based on these facts, one way to keep up with the rapid developments in science and technology is to always access up-to-date information and all of this can be obtained via the internet.